The conformation of acetylcholine at its target site in the membrane-embedded nicotinic acetylcholine receptor. - Williamson, P; Verhoeven, A; Miller, K; Meier, B; Watts, A (2007)
The conformation of the neurotransmitter acetylcholine bound to the fully functional nicotinic acetylcholine receptor embedded in its native membrane environment has been characterized by using frequency-selective recoupling solid-state NMR. Six dipolar couplings among five resolved (13)C-labeled atoms of acetylcholine were measured. Bound acetylcholine adopts a bent conformation characterized with a quaternary ammonium-to-carbonyl distance of 5.1 A. In this conformation, and with its orientation constrained to that previously determined by us, the acetylcholine could be docked satisfactorily in the agonist pocket of the agonist-bound, but not the agonist-free, crystal structure of a soluble acetylcholine-binding protein from Lymnaea stagnali. The quaternary ammonium group of the acetylcholine was determined to be within 3.9 A of five aromatic residues and its acetyl group close to residues C187/188 of the principle and residue L112 of the complementary subunit. The observed >C O chemical shift is consistent with H bonding to the nicotinic acetylcholine receptor residues gammaY116 and deltaT119 that are homologous to L112 in the soluble acetylcholine-binding protein.